Cartilage Thickness in the Hip Measured by MRI and Stereology Before and After Periacetabular Osteotomy - Mechlenburg, Inger (Springer-Verlag, 2010)
BACKGROUND: Untreated hip dysplasia can result in a degenerative process joint and secondary osteoarthritis at an early age. While most periacetabular osteotomies (PAOs) are performed to relieve symptoms, the osteotomy is presumed to slow or prevent degeneration unless irreparable damage to the cartilage has already occurred. QUESTIONS/PURPOSES: We therefore determined (1) whether changes in the thickness of the cartilage in the hip occur after PAO, and (2) how many patients had an acetabular labral tear and whether labral tears are associated with thinning of the cartilage after PAO. PATIENTS AND METHODS: We prospectively followed 22 women and four men with hip dysplasia with MRI before PAO and again 1 year and 2½ years postoperatively to determine if cartilage thinning (reflecting osteoarthritis) occurred. The thickness of the femoral and acetabular cartilage was estimated with a stereologic method. Three and one-half years postoperatively, 18 of 26 patients underwent MR arthrography to investigate if they had a torn acetabular labrum. RESULTS: The acetabular cartilage thickness differed between 1 and 2½ years postoperatively (preoperative 1.40 mm, 1 year postoperatively 1.47 mm, and 2½ years postoperatively 1.35 mm), but was similar at all times for the femoral cartilage (preoperative 1.38 mm, 1 year postoperatively 1.43 mm, and 2½ years postoperatively 1.38 mm.) Seventeen of 18 patients had a torn labrum. The tears were located mainly superior on the acetabular rim. CONCLUSION: Cartilage thickness 2½ years after surgery compared with preoperatively was unchanged indicating the osteoarthritis had not progressed during short-term followup after PAO.